2004
DOI: 10.1016/j.ydbio.2004.04.033
|View full text |Cite
|
Sign up to set email alerts
|

The role of mechanical forces in dextral rotation during cardiac looping in the chick embryo

Abstract: Cardiac looping is a vital morphogenetic process that transforms the initially straight heart tube into a curved tube normally directed toward the right side of the embryo. While recent work has brought major advances in our understanding of the genetic and molecular pathways involved in looping, the biophysical mechanisms that drive this process have remained poorly understood. This paper examines the role of biomechanical forces in cardiac rotation during the initial stages of looping, when the heart bends a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
182
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 120 publications
(201 citation statements)
references
References 37 publications
18
182
0
1
Order By: Relevance
“…Statistical significance was confirmed by 2 test (P Ͻ 0.025). These results support previous notions that the OVs play a key role in establishing left-right directionality, with both OVs tending to push the heart to the opposite side (Voronov et al, 2004). In addition, we speculate that asymmetric contraction of the conotruncus ensures rightward looping when both veins are absent.…”
Section: Crucial Contraction Occurs Near the Ends Of The Heart Tubesupporting
confidence: 92%
See 4 more Smart Citations
“…Statistical significance was confirmed by 2 test (P Ͻ 0.025). These results support previous notions that the OVs play a key role in establishing left-right directionality, with both OVs tending to push the heart to the opposite side (Voronov et al, 2004). In addition, we speculate that asymmetric contraction of the conotruncus ensures rightward looping when both veins are absent.…”
Section: Crucial Contraction Occurs Near the Ends Of The Heart Tubesupporting
confidence: 92%
“…During c-looping, the heart tube undergoes ventral bending and dextral torsion to create a cshaped tube, with the outer (convex) curvature normally directed toward the right side of the embryo (Mä nner, 2000). Previous work has shown that bending is driven primarily by morphogenetic forces that arise within the heart tube (Butler, 1952;Manning and McLachlan, 1990;Latacha et al, 2005), but torsion is caused by loads exerted on the heart by neighboring tissues (Voronov et al, 2004). The present study illustrates the inadequacy of this dichotomous perspective, revealing a causal relationship between forces acting on the heart and those developed within the heart.…”
Section: Introductionmentioning
confidence: 45%
See 3 more Smart Citations